Extended benefit entitlement periods and the duration of unemployment in West Germany - Viktor Steiner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1997)
Germany1, as most other European countries, has been plagued by a persistently high level of long?term unemployment since the early 1980's. In contrast, long? term unemployment is much less of a problem in the United States. One potential reason for the different structure of unemployment relates to institutional differences in unemployment compensation systems. The German system is characterized by relatively high income?replacement ratios and extended benefit?entitlement periods which are often followed by the availability of open?ended unemployment or social assistance schemes. In contrast, unemployment insurance payments in the United States are terminated after about six months as a rule, and entitlement to subsequent welfare payments are only available to lone mothers and the disabled. Can these institutional differences explain the higher level of long?term unemployment in Germany relative to the United States?
Keywords: 330; Arbeitslosenversicherung; Arbeitslosigkeit; Langzeitarbeitslosigkeit; Arbeitsangebot; Arbeitsuche; Schätzung; Deutschland